A theory of the relationships between foreign direct investment and trade - Pontes, José Pedro (2022)
Although empirical evidence shows that the relationship between foreign direct investment (FDI) and trade is complex, theories of international investment (both vertical and horizontal) present simple patterns of relation. By allowing for different locations of vertically-related stages of production and distinguishing between trade in finished goods and trade in intermediate goods, this paper introduces a nonmonotonic relationship between multinational firms and trade costs, which must be neither too high nor too low for FDI to arise. Exports and FDI behave as complements for high levels of trade costs and as substitutes otherwise.